MR imaging of patients with lateral epicondylitis of the elbow: is the common extensor tendon an isolated lesion? - Liang Qi (PLoS ONE, 2013)
OBJECTIVE: To investigate whether an injury of the common extensor tendon (CET) is associated with other abnormalities in the elbow joint and find the potential relationships between these imaging features by using a high-resolution magnetic resonance imaging (MRI). METHODS: Twenty-three patients were examined with 3.0 T MR. Two reviewers were recruited for MR images evaluation. Image features were recorded in terms of (1) the injury degree of CET; (2) associated injuries in the elbow joint. Spearman's rank correlation analysis was performed to analyze the relationships between the injury degree of CET and associated abnormalities of the elbow joint, correlations were considered significant at p<0.05. RESULTS: Total 24 elbows in 23 patients were included. Various degrees of injuries were found in total 24 CETs (10 mild, 7 moderate and 7 severe). Associated abnormalities were detected in accompaniments of the elbow joints including ligaments, tendons, saccussynovialis and muscles. A significantly positive correlation (r = 0.877,p<0.01) was found in injuries of CET and lateral ulnar collateral ligament (LUCL). CONCLUSION: Injury of the CET is not an isolated lesion for lateral picondylitis, which is mostly accompanied with other abnormalities, of which the LUCL injury is the most commonly seen in lateral epicondylitis, and there is a positive correlation between the injury degree in CET and LUCL.